2017
DOI: 10.1200/jco.2017.73.4830
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ALK With Crizotinib in Pediatric Anaplastic Large Cell Lymphoma and Inflammatory Myofibroblastic Tumor: A Children’s Oncology Group Study

Abstract: Purpose Fusions involving the ALK gene are the predominant genetic lesion underlying pediatric anaplastic large cell lymphomas (ALCL) and inflammatory myofibroblastic tumors (IMTs). We assessed the activity of the ALK inhibitor crizotinib in patients who had no known curative treatment options at diagnosis or with relapsed/recurrent disease. Methods In this study, 26 patients with relapsed/refractory ALK-positive ALCL and 14 patients with metastatic or inoperable ALK-positive IMT received crizotinib orally twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
317
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(327 citation statements)
references
References 29 publications
2
317
1
7
Order By: Relevance
“…When including our two patients, we were able to retrieve detailed information of a total of 16 patients (nine male and seven female). In addition, a recent study by the Children´s Oncology Group (COG) reported on 14 patients with ALK + IMT to receive crizotinib, some of whom had been included in a previous phase I/II study . However, these studies did not report individual patient data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When including our two patients, we were able to retrieve detailed information of a total of 16 patients (nine male and seven female). In addition, a recent study by the Children´s Oncology Group (COG) reported on 14 patients with ALK + IMT to receive crizotinib, some of whom had been included in a previous phase I/II study . However, these studies did not report individual patient data.…”
Section: Resultsmentioning
confidence: 99%
“…The median age of the 16 patients included in case reports was 22 years (range 4–71 years), and five patients were younger than 18 years . The median age of the children included in the COG study was 7 years (range 2–13.5 years) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while these targeted agents have shown good response rates, there are still patients who eventually relapse especially after the discontinuation of treatment and thus need other therapies . Thus, these drugs are now mostly used as a bridge for transplantation or as a life‐long therapy …”
mentioning
confidence: 99%
“…В работе Y.P. Mosse было показано, что при использовании кризотиниба в дозе 165 мг/м 2 у больных с рецидивом АККЛ ALK+ частота ПР со-ставила 83 % [33]. Предложены схемы лечения, вклю-чающие кризотиниб и винбластин для лечения реци-дивов АККЛ у детей [34].…”
unclassified